Ecosystem service bundles under SSP-RCP and local scenarios: A pathway to comprehensive spatial planning for sustainability - Shihao Zhou; Yilun Qu; Yixiang Wang; Zhaoping Wu; Yan Shi (Resources, Environment and Sustainability)
Global and local efforts have each made significant contributions to advancing sustainable development, yet systematic research on the role of global strategies in guiding local practices remains scarce. This study takes the Yangtze River Delta urban agglomerations as a case study and introduces an innovative framework that integrates global perspectives with local practices. By conducting a comparative analysis of ecosystem service (ES) bundles under the climate change scenario and a local scenario group, the study identifies critical pathways for optimizing future spatial planning. The findings suggest that merely increasing ESs supply is not the primary objective of the local spatial management, addressing key trade-offs among ESs should take precedence. For instance, promoting sustainable agriculture can mitigate conflicts between ESs, reduce boundaries between woodland and cropland, foster synergies among multiple ESs, and alleviate the imbalance in ecological development between the northern and southern regions. In highly urbanized areas, the growth of urban green spaces can also contribute positively to sustainable development. This framework not only bridges the gap between global strategies and local sustainable development practices but also expands the application of ES bundles in spatial planning and management. It offers new theoretical insights and practical solutions for achieving sustainability.